2015
DOI: 10.3758/s13415-015-0350-y
|View full text |Cite
|
Sign up to set email alerts
|

Learning the opportunity cost of time in a patch-foraging task

Abstract: Although most decision research concerns choice between simultaneously presented options, in many situations options are encountered serially and the decision is whether to exploit an option or search for a better one. Such problems have a rich history in animal foraging but we know little about the psychological processes involved. In particular, it is unknown whether learning in these problems is supported by the well studied neurocomputational mechanisms involved in more conventional tasks. We investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

37
319
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 183 publications
(359 citation statements)
references
References 77 publications
(149 reference statements)
37
319
1
2
Order By: Relevance
“…In each model, was initialized at the beginning of the experiment to the arithmetic average reward rate across the experiment, but subsequently carried over between environments (Constantino and Daw, 2015;Garrett and Daw, 2019). For each participant, we estimated the free parameters of the To formally test for differences in learning rates ( p , M ) we estimated the covariance matrix Σ x over the group level parameters using the Hessian of the model likelihood (Oakes, 1999) and then used a contrast c z Σ x c to compute the standard error on the difference p -M .…”
Section: Analysis Branch 2 -Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In each model, was initialized at the beginning of the experiment to the arithmetic average reward rate across the experiment, but subsequently carried over between environments (Constantino and Daw, 2015;Garrett and Daw, 2019). For each participant, we estimated the free parameters of the To formally test for differences in learning rates ( p , M ) we estimated the covariance matrix Σ x over the group level parameters using the Hessian of the model likelihood (Oakes, 1999) and then used a contrast c z Σ x c to compute the standard error on the difference p -M .…”
Section: Analysis Branch 2 -Methodsmentioning
confidence: 99%
“…Recent work in humans further resolves the computational challenge of learning dynamic environmental richness, by demonstrating that sequential choice behavior is best captured by an MVT inspired learning model. Specifically, both decisions to leave a patch and explore the environment in patch foraging (Constantino and Daw, 2015;Lenow et al, 2017) and capture behavior in prey selection (Garrett and Daw, 2019) adhere to the MVT predicted optimality policy that compares yields against fluctuating environmental richness which is learned via a standard delta rule. This later work further demonstrated that beliefs about environmental richness update with asymmetric bias, whereby improvements are learned at a higher rate than deteriorations; the 'naïve perseverance of optimism' (Garrett and Daw, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…La decisión implica el optar por una opción, o conjunto de ellas, pero en tal elección lo que se evalúa en realidad es la renuncia o perdida por preferir un camino o ruta por sobre otras posibilidades (Spiller, 2011). Ya sea que se trate de una empresa o un individuo, distintas variables se incluyen en la noción del costo de oportunidad, y cada sujeto posee sus propios imaginarios acerca de tales variables, pero en términos generales, dos aspectos son tenidos en cuenta por parte del decisor cuando su elección se realiza en función alcosto de oportunidad: tiempo y dinero (Constantino y Daw, 2015;Frederick, Novemsky, Wang, Dhar y Nolwis, 2009;Mogilner y Aaker, 2009;Monga y Saini, 2009;Okada y Hoch, 2004;Payne, Bettman y Luce, 1996;Sanabria, Thrailkill y Killeen, 2009).…”
Section: Costo De Oportunidadunclassified